Spectroscopy and photophysics of 4- and 7-hydroxycoumarins and their thione analogs - Seixas de Melo, J. (2001)
Acid-base equilibria were studied for 4-hydroxycoumarin, 7-hydroxy-4-methylcoumarin and their thione derivatives in different media for their ground and lowest energy singlet and triplet excited states. The ethoxylated and/or methoxylated derivatives were also investigated. Characterization involves fluorescence spectra, quantum yields, lifetimes, phosphorescence spectra, lifetimes, and triplet-triplet absorption spectra. From their pKa values it was found that 4 and 7-hydroxycoumarins are more acidic in their lowest excited singlet states than in S0. The origin and character of the lowest singlet and triplet excited states is discussed.